The mitochondrial genomes of Iberian freshwater and diadromous fishes - Veríssimo, Joana (2025)
The Iberian Peninsula, in southwestern Europe, is home to a distinctive freshwater fish fauna, predominantly composed of endemic species. This is a consequence of the prolonged isolation from western Europe caused by the Pyrenees, the diverse geological and climatic gradients, and the isolation of river basins. Freshwater and diadromous fishes have diversified in the Iberian Peninsula and include 72 currently recognized native species, 50 of which are endemic to the region. Habitat loss and degradation, the introduction of invasive species, and climate change have placed Iberian freshwater and diadromous fishes among the most threatened groups of vertebrates, with some species on the brink of extinction. Here, we present 60 new complete mitochondrial genome assemblies out of the 109 freshwater and diadromous fish species found in the Iberian Peninsula, including the mitogenomes of 37 endemics. These resources are crucial for characterising the mitochondrial evolution of species, reconstructing phylogeny and paleogeography, advancing species identification, delineation, and monitoring, and ultimately supporting conservation planning.